(untitled) (American Journal of Economics and Business Innovation, 2024)
The current economic structure in the West is presented in this study as the product of a meeting of Marxist and Derridean ideas. In the light of this intersection and their variance, this study aims to contrast the economic views of Marx and Derrida with those of mainstream capitalism, to assess Derrida’s philosophical grounds for doubting the stability of Western economic structures, to understand the implications of adopting the Marxist perspective in the Western economic system, to examine how Marxist New International Politics and Derrida’s philosophy intersect, and what it means for international trade relations and global economic control. The study’s discourse was informed by the principles of Neoclassical economics to accomplish these objectives. The research used a systematic review process, with the PRISMA criteria utilized to guide the selection and screening of articles, hence, N = 482, n = 32. While 34% of the screened publications were found in Google Scholar (GS), the years 2015, 2019, and 2022 accounted for 57% of the cited papers. The research also used thematic analysis, delving deeply into four themes: Marx’s criticism of capitalism, Derrida’s deconstruction of capitalism, power and hegemonic dynamics, globalization and neoliberalism. The study findings show that Marx’s ideal economic system is one in which production choices are made by centralized authorities rather than the exploitative capitalist market. While Derrida agrees with the Marxist negative perspectives of capitalism, thus establishing an intersection, he argues that the transition from a capitalist system to an alternative society may cause considerable economic problems, thus advocating for improvements and not a switch. The study contends that the synthesis of the capitalist system’s positive and negative qualities has had a significant impact on the argument between Marxist and Derridean scholars and this link has established a framework for more research in economics.